2019
DOI: 10.1063/1.5084031
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress on high power impulse magnetron sputtering (HiPIMS): The challenges and applications in fabricating VO2 thin film

Abstract: High power impulse magnetron sputtering (HiPIMS) is well known in modern physical vapor deposition (PVD) owing to its high peak power density, high degree of ionization, high plasma density and hence high ion flux towards the substrate that allows ones to deposit high quality thin films in comparison with conventional magnetron sputtering technology. The present short review on HiPIMS intends to provide readers with a summary of the current status of this emerging PVD technique: the developmental history, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 82 publications
2
15
0
Order By: Relevance
“…In this paper, the fabrication of epitaxial GeSn layers by using high power impulse MS (HiPI-MS) is reported for the first time. Higher crystalline quality of epitaxial GeSn is obtained by HiPI-MS in comparison to the conventional RF-MS method, in agreement with published results for other materials . Heterostructures of epitaxial GeSn alloys and GeSn NCs embedded in oxide matrix are obtained by one run of MS deposition, and the formation of p–n heterojunctions is given by the intrinsic layer properties.…”
Section: Introductionsupporting
confidence: 88%
“…In this paper, the fabrication of epitaxial GeSn layers by using high power impulse MS (HiPI-MS) is reported for the first time. Higher crystalline quality of epitaxial GeSn is obtained by HiPI-MS in comparison to the conventional RF-MS method, in agreement with published results for other materials . Heterostructures of epitaxial GeSn alloys and GeSn NCs embedded in oxide matrix are obtained by one run of MS deposition, and the formation of p–n heterojunctions is given by the intrinsic layer properties.…”
Section: Introductionsupporting
confidence: 88%
“…Rezek et al [ 42 ] observed that resistivity significantly decreases with increasing pulsed-averaged target power density up to 950 W/cm 2 as a result of decreasing the grain size in film microstructure. In other studies, the bias voltages were frequently applied to the substrate to control the electron bombardment momentum and thus, to improve the film properties [ 63 ]. Since the negative ion energy depend strongly on the self-bias, it is stated that negative oxygen ions are one of the factors significantly influencing thin film properties [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…The surface was observed more uniform with an average height of the grain at around 2 nm. In Sample A , droplets still exist as the DC and HiPIMS sometimes having an arching phenomenon if the stable plasma not achieved (Zhang et al , 2019). However, the heat assistance was observed to help to reduce the effect of droplets as shown in Sample B .…”
Section: Resultsmentioning
confidence: 99%
“…Another type of magnetron sputtering called high-power impulse magnetron sputtering (HiPIMS) introduced in 1991 that uses the pulse power plasma discharge (Kouznetsov et al , 1999). HiPIMS known to generate a high plasma density as the high degree of ionization achieved due to peak power that exceeded the time-average power (Zhang et al , 2019). The high degree of ionization resulting a dense and smooth surface of thin-film as compared to DC and RF reactive sputtering.…”
Section: Introductionmentioning
confidence: 99%